Assessing the effect of acid and alkali treatment on a halloysite-based catalyst for dry reforming of methane - Ahmed Abotaleb (9596108) (2024)
Dry reforming of methane (DRM) has recently received wide attention owing to its outstanding performance in the reduction and conversion of CH4 and CO2 to syngas (H2 and CO). From an industrial perspective, nickel (Ni)-supported catalysts have been deemed among the most suitable catalysts for DRM owing to their low cost and high activity compared to noble metals. However, a downside of nickel catalysts is their high susceptibility to deactivation due to coke formation and sintering at high temperatures. Using appropriate supports and preparation methods plays a major role in improving the activity and stability of Ni-supported catalysts. Halloysite nanotubes (HNTs) are largely utilized in catalysis as a support for Ni owing to their abundance, low cost, and ease of preparation. The treatment of HNTs (chemical or physical) prior to doping with Ni is considered a suitable method for increasing the overall performance of the catalyst. In this study, the surface of HNTs was activated with acids (HNO3 and H2SO4) and alkalis (NaOH and Na2CO3 + NaNO3) prior to Ni doping to assess the effects of support treatment on the stability, activity, and longevity of the catalyst. Nickel catalysts on raw HNT, acid-treated HNT, and alkali-treated HNT supports were prepared via wet impregnation. A detailed characterization of the catalysts was conducted using X-ray diffraction (XRD), BET surface area analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), solid-state nuclear magnetic resonance (ssNMR), H2-temperature programmed reduction, (H2-TPR), CO2-temperature programmed desorption (CO2-TPD), and Ni-dispersion via H2-pulse chemisorption. Our results reveal a clear alteration in the structure of HNTs after treatment, while elemental mapping shows a uniform distribution of Ni throughout all the different supports. Moreover, the supports treated with a molten salt method resulted in the overall highest CO2 and CH4 conversion among the studied catalysts and exhibited high stability over 24 hours testing. Other Information Published in: RSC Advances License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1039/D3RA07990B Additional institutions affiliated with: Core Labs - HBKU